Is research for development a good investment? Reflections on lessons from the NBDC - Merrey, Douglas J. (International Livestock Research Institute, 2013)
‘Integrated Research for Development’ has been promoted as an approach to research and development in natural resources management that is most likely to lead to positive impacts. It has various acronyms, e.g. ‘INRM’ and ‘R4D.’ It was the underlying theory of the SSA Challenge Program, managed by FARA and implemented by CGIAR centres and African partners. R4D was a basis for the first phase of CPWF, though in a rudimentary form. It was adopted as the theoretical basis for CPWF phase II. All six basin challenges are based on R4D, including NBDC. All six BDCs promise significant outcomes leading ultimately to poverty reduction and environmental conservation through application of R4D. It is time for a critical review of the lessons learned from the investments in R4D, particularly as it is being adopted as the underlying theory of the new CGIAR Research Programs. This paper is an early contribution to this review. It examines the premises, promises and actual achievements to the extent possible, using the NBDC as a case study. It identifies critical lessons that should inform future R4D programs. The author draws on nearly 35 years of experience in applied water management research, including the CPWF from its early phase and what he has learned from his engagement with the NBDC, including recent work contributing to the NBDC Institutional History (future versions of this paper may include other co-authors, but the present version represents only the author’s views). The paper briefly examines the roots of R4D in earlier incarnations of ‘action research’ and identifies what is ‘new’: the wide range of diverse partnerships involved in the research. In NBDC and most likely the other BDCs, such diversity brings important challenges that have only partially been solved, as well as new opportunities that have only partially been realized. Future R4D programs will be good investments only under certain conditions. These include effective partnerships; strong commitment from the demand side institutions, including their empowerment vis-àvis the researchers; long-term commitment by funding agencies with periodic reviews to guide the direction of the program; strong links to existing development investment programs; and an excellent science foundation.